Entrepreneurship-Based Human Resource Development Management Model at Al-Ghoniyyah Islamic Boarding School in Selaawi, Garut, to Achieve Sustainable Economic Independence - Imam Dzulfikris Salim; Ahmad Sukandar (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to deeply analyze the human resource development management model based on entrepreneurship at Pondok Pesantren Al-Ghoniyyah Selaawi, Garut. The research is motivated by the challenges faced by salafiah pesantrens in achieving economic independence without abandoning their Islamic traditional identity amid global changes, with only 15% of the 1,010 pesantrens in Garut operating sustainable business units. This research examines how the integration of the salafiah curriculum (Nahwu-Sharf, Fiqh, and Qur’an memorization) with student entrepreneurship programs can enhance the economic capacity of pesantrens. Using an intrinsic qualitative case study approach, data were collected through six months of participatory observation, in-depth interviews with kyai, management, students, business partners, as well as an analysis of financial documents and the Pesantren Endowment Fund (DAP) policies. The results show that implementing the Spiritual Entrepreneurship Management (SEM) model—which incorporates a syirkah muḍārabah profit-sharing system, quarterly sharia audits, marketing digitalization using the “PesantrenTech” platform, and collaboration with the Al-Ghoniyyah Center Foundation—led to a 121% increase in pesantren revenue over three years and encouraged 78% of graduate students to become independent entrepreneurs. The study recommends replicating the SEM model in other pesantrens throughout Garut by optimizing the DAP and synchronizing with the West Java OPOP (One Pesantren One Product) program. The findings assert that the integration of spiritual values, modern human resource management, and cross-sector partnerships is the key to strengthening pesantren economic independence based on Islamic values and local wisdom.